Reseña de Justice in Physical Education: Critical Reflections and Pedagogies for Change - Martínez Baena, Alejandro (Profesorado, Revista de Currículum y Formación del Profesorado, 2018)
Recensión de: Robinson, D. B. y Randall, L. (2016). Social Justice in Physical Education: Critical Reflections and Pedagogies for Change. Toronto: Canadian Scholars´ Press Inc.